The Cooling Load Calculation Using E20 Spreadsheet and HAP Software for for the Main Entrance Glass Atrium of Shopping Mall Building - ISA, ISMA FATIN ALIA; Sies, Ts. Dr. Mohamad Farid (Research Progress in Mechanical and Manufacturing Engineering, 2023)
A complete air conditioning system has been developed to control ambient conditions such as relative humidity, temperature, and movement in an atrium shopping mall building in Batu Pahat, Johor. This study focuses on cooling load estimation of the building by using two calculation methods. The calculation will consider the ASHRAE standards to ensure that valid results and data are achieved. The objective of this study is to calculate the cooling load using Hourly Analysis Program (HAP software) and manual calculation. The manual calculation will be conducted using E20 Spreadsheet. The building consists of four floors, and 44 shop lots must be conditioned. The cooling loads on people, infiltration, lighting, ventilation heat gain, roofs, and walls can also be easily entered into the E20 Spreadsheet. At the end of this study, the result shows that the total cooling loads using two different methods are similar. The maximum difference in total cooling load between manual calculation and HAP software is 2.3 percent. Therefore, the research can be extended to many buildings such as schools, restaurants, hospitals, and others to improve the current research outcome.